Effect of High-Flow Nasal Cannula for Hypoxemia Following Sun's Procedure in Acute Aortic Dissection Type a Patients - Yan, ChaoJun; Zhang, Jianrong; Wu, Yi; Yao, Jie; Li, Jun; Zhang, Xianpu; Cheng, Yongbo; Liu, Xin; Yi, Jianguang; Lin, Deqin; Yu, Sanjiu; Guo, Mei; et al. (Frontiers in Surgery, 2021)
BACKGROUND:Acute aortic dissection type A (AADA) patients who had Sun's procedure often suffer from hypoxemia(PaO2/FiO2<300 mmHg) before weaning in ICU. OBJECTIVE: The study analyzed the efficacy of high-flow nasal cannula (HFNC) for hypoxemia before weaning following Sun’s procedure in comparison with the conventional oxygen therapy (COT). METHODS: The medical records of 87 adult AADA patients who only underwent Sun's procedure and met the inclusion criterion of PaO2/FiO2<300 mmHg before weaning were retrospectively analyzed (41 patients were treated with HFNC and 46 were treated with COT). The oxygenation level, fraction of inspired oxygen (FiO2), PaCO2, HR, RR, subjective discomfort and reintubation rate were recorded. The difference of lung volume loss between HFNC and COT groups was calculated by 3D reconstruction of CT images and assessed by radiological atelectasis score ( chest X-ray) respectively. RESULTS: From day 1 to day 5 after weaning, there was no significant difference in PaO2/FiO2 (SpO2/FiO2) between the HFNC group and COT group, but FiO2 of the HFNC group was significantly lower than that of COT group (P<0.05). Further studies indicate that the percentage of lung volume loss (pleural effusion and/or pulmonary atelectasis) by 3D reconstruction of CT images at 4-8 days postoperation was significantly lower in the HFNC group (P<0.05). The subjective discomfort of HFNC group was significantly reduced, and the rate of reintubation and length of stay in ICU were significantly lower than those of COT group (P<0.05). There was no significant difference in readmitted to ICU and in-hospital mortality between the two groups. CONCLUSIONS: HFNC can be used as a effective oxygen therapy for patients with hypoxemia in Sun's procedure.